Aplicación del proceso enfermero a la práctica asistencias en el caso clínico de infección de vías urinarias. - Soto Sarango, Ángel Javier (2013)
The aim of the NANDA International, is to strengthen the development of nursing knowledge. In the present study, the steps of the nursing process is applied from assessment using the 11 Functional Health Patterns Marjory Gordon , the diagnosis was established using the NANDA International taxonomy and NOC linkage and NIC that guided the identification and implementation nursing actions. The study was prospective, descriptive qualitative. In an 11 months old, was applied to a case of female entry into service with Pediatrics Medical Diagnosis of Urinary Tract Infection. Such analysis, Nursing Diagnoses NANDA I: Constipation related to change in eating pattern manifested by abdominal distension (Code 00011) (girl), parental impairment related to low socioeconomic class, manifested by frequent illnesses (Code 00056) (Little-family); dysfunctional family processes related to lack of skills for solving problems, manifested by increasing conflict (Code 00063) (family), stress-related anxiety manifested by nervousness (Code 00146) (Mother), the NOC: Bowel Elimination (girl) (Code 0501), Implementation of the role of parents (girl-family) (Code 2211), Coping with family problems (family) (Code 2600), anxiety level (Mother) (Code 1211) , same that guided nursing actions. Finally according to the assessment of the results by the Likert scale, the indicators are still at risk are: Implementation of the role of parents (Code 2211) with a risk of rarely shown and anxiety level (Code 1211) with a substantial risk. KEYWORDS: Process RN, Urinary tract infection, Taxonomy NANDA, Nursing Interventions